Conjoined twin (Bangladesh Medical Journal Khulna, 2017)
In the recent past we encountered a pair of newborn who were symmetrically conjoined. We found a 30 years old woman who delivered those conjoined babies by caesarean section at full term. Antenatal ultrasonography at 26 weeks revealed twin pregnancy but no comment regarding conjunction. After delivery, babies were found fuse from upper thorax to umbilical region. Postnatal ultrasonography revealed single liver. Till date many such cases have been reported worldwide but so far no case report has been published in our country. Bang Med J (Khulna) 2016; 49 : 40-42